A Case-Control Study of Keratoconus Risk Factors. Issue 6 (June 2020) - Moran, Sarah; Gomez, Ludovic; Zuber, Kevin; Gatinel, Damien
Abstract : Purpose: To evaluate risk factors associated with keratoconus in a case-control setting. Methods: This single center, prospective, case-control study was carried out from May 2014 to November 2017 at the Rothschild Foundation (Paris, France). Two hundred two patients with keratoconus and 355 control patients were investigated and followed by a single ophthalmologist. Data regarding multiple variables were gathered, including eye rubbing, pattern of eye rubbing, dominant hand, allergies, history of dry eye, screen time, sleep position, and night-time work. Results: After multivariable analysis, the following variables showed significant results: eye rubbing with knuckles [odds ratio (OR) = 8.29; 95% confidence interval (CI): 3.92–18.26, P < 0.001] or fingertips (OR = 5.34; 95% CI: 2.44–12.21, P < 0.001), a history of dry eye (OR = 4.16; 95% CI: 2.3–7.7; P < 0.001), male sex (OR = 4.16; 95% CI: 1.47–11.89; P < 0.001), screen time (OR = 1.02; 95% CI: 1.01–1.04; P < 0.001), prone sleep position (OR = 11.63; 95% CI: 3.88–38.16), and side sleep position (OR = 10.17, 95% CI 3.84–33.73). Conclusions: This study shows a strong correlation between eye rubbing and keratoconus, particularly when rubbing is performed with the knuckles. Additional associations were identified which may merit future investigation as risk factors, including sleep position, night-time work, and screen time.